1995
DOI: 10.1002/hbm.460030403
|View full text |Cite
|
Sign up to set email alerts
|

A PET investigation of implicit and explicit sequence learning

Abstract: Abstract:The purpose of this study was to determine the mediating neuroanatomy of implicit and explicit sequence learning using a modified version of the serial reaction time (SRT) paradigm. Subjects were seven healthy, right-handed adults (three male, four female, mean age 26.7, range 1843 yr). PET data were acquired via the oxygen-15-labeled-carbon dioxide inhalation method while subjects performed the SRT. Subjects were scanned during two blocks each of I) no sequence (Random), 2 ) single-blind, 12-item seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
154
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 221 publications
(170 citation statements)
references
References 54 publications
(41 reference statements)
14
154
1
1
Order By: Relevance
“…Our study is also supported by the findings of Rauch et al (1995), who showed that the neuronal correlates of explicit and implicit learning were different. In this context, we might hypothesize that the primary visual and inferior parietal cortices (which are specific to explicit learning) would not have been involved in the participants' performance in Experiment 2, neither in the incidental-learning nor in the explicit-learning condition; indeed, as we have shown, the participants in the explicit-learning conditions could not use the explicitly learned information.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study is also supported by the findings of Rauch et al (1995), who showed that the neuronal correlates of explicit and implicit learning were different. In this context, we might hypothesize that the primary visual and inferior parietal cortices (which are specific to explicit learning) would not have been involved in the participants' performance in Experiment 2, neither in the incidental-learning nor in the explicit-learning condition; indeed, as we have shown, the participants in the explicit-learning conditions could not use the explicitly learned information.…”
Section: Discussionsupporting
confidence: 90%
“…They concluded that learning a probabilistic sequence depends essentially on implicit-learning mechanisms. Rauch et al (1995) also showed in a PET study that the cerebral structures activated when the sequence is learned explicitly differ from those activated when the sequence is learned incidentally. According to this study, the regions involved in the incidental-learning condition are the right ventral premotor cortex, the right ventral caudate/nucleus accumbens, the right thalamus, and the bilateral Area 19; in the explicit-learning condition, the areas known to play a role in visual and language processes are involved (i.e., the primary visual and inferior parietal cortex).…”
Section: Methodsmentioning
confidence: 93%
“…The results of the motor sequence group show that it is not implicit learning in general that recruits MTL structures, but only those related to perceptual learning. In contrast, motor sequence learning involved the basal ganglia and motor cortex, which has previously been reported in SRT paradigms (Grafton et al, 1995;Rauch et al, 1995;Berns et al, 1997;Hazeltine et al, 1997;Peigneux et al, 2000;Willingham et al, 2002).…”
Section: Discussionmentioning
confidence: 62%
“…Neuroimaging studies reported controversial results regarding the participation of MTL structures during SRT learning. Most studies observed activation in the putamen and the striatum (Grafton et al, 1995;Rauch et al, 1995;Berns et al, 1997;Hazeltine et al, 1997;Peigneux et al, 2000;Willingham et al, 2002). However, a recent study demonstrated MTL activation during implicit and explicit SRT learning (Schendan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not commonly seen as a critical component of sequence learning. In contrast, the striatum is known to participate in implicit sequence learning (Grafton et al, 1995;Rauch et al, 1995;Rauch et al, 1997) and specifically in the encoding of the temporal context set by the previous stimulus in the probabilistic SRT task . The finding that the strength of the functional connections between cuneus and striatum is increased during post-training REM sleep suggests the involvement of the basal ganglia in the off-line reprocessing of implicitly acquired high-order sequential information.…”
Section: Functional Relationships Between Rem Sleep and The Processinmentioning
confidence: 99%